Developing Video Copywriting for Ketek Wisata @3 Palembang as a Tourism Destination - Ananda Salsabilah; Muhammad Nadjmuddin; Sunani; Zidni Ma`ruf; Siti Rahayu; Rizky Aliansyah (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
This study examined the development of a promotional video script for Ketek Wisata @3 Palembang, a traditional boat tour that showcased the cultural heritage of the Musi River. The primary objective was to produce a persuasive, narrative-driven script aimed at attracting both domestic and international tourists. The study adopted the Research and Development (R&D) method proposed by Sukmadinata (2017), which involved three main stages: preliminary study, product development, and final testing. The unit of analysis was a bilingual video script written in both English and Indonesian, structured according to the AIDA model (Attention, Interest, Desire, Action). Data were gathered through observation, interviews, and documentation. The analysis was carried out using a qualitative descriptive approach, drawing on insights from expert evaluations. The findings indicated that it is necessary to integrate cultural storytelling, visual support, and persuasive narrative element. Expert feedback validated the script's clarity and linguistic accuracy. The final product served as a replicable framework for promoting local tourism via digital platforms such as YouTube and TikTok. It was recommended that future promotional efforts continue to involve local community perspectives and uphold cultural authenticity to further strengthen tourism visibility. Keywords: Tourism, Video Copywriting, Musi River, Digital Marketing, Narrative Script   DOI: https://doi.org/10.5281/zenodo.17837602